ANALISIS PERBANDINGAN PUTUSAN PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG (T.P.P.O) (STUDI PUTUSAN NOMOR 632 K/PID.SUS/2016 DAN PUTUSAN NOMOR 1447K/ PID.SUS/ 2016) - Saras Sulistyawati (Jurnal Ilmiah Dinamika Hukum, 2018)
Human Trafficking is an act of recruitment, shelter, sending, transferring, or accepting someone with the threat of violence, using violence, kidnapping, confinement, counterfeiting, fraud, abuse of power or vulnerable positions, debt bondage or paying or benefits, so obtain approval from the person who holds control over the other person, whether carried out within the state or between countries, for the purpose of exploitation or to result in exploitation (Law Number 21 of 2007 concerning the Eradication of Crimes in Trafficking in Persons). This study aims to analyze aspects of judges' consideration of the criminal termination of perpetrators of trafficking in persons in Decision Number 632.K / PID.SUS / 2016 and Decisions Number 1447.K / PID.SUS / 2016, covering juridical, philosophical, and sociological aspects. Juridical aspects are based on the existing legal umbrella and judge as the applicator, sociological aspects, namely the application of the law concerning the values ​​of society in order to create legal justice, and philosophical aspects that are based on the value of truth and justice. This research is a type of normative juridical research that focuses on studying the application of positive legal norms or norms. The problem in this study regarding the basis of the judge's consideration in imposing criminal sanctions against perpetrators of trafficking in persons and the comparison of judges' considerations related to criminal imposition of perpetrators of human trafficking in decisions No. 632.K / PID.SUS / 2016 and Decisions Number 1447.K / PID.SUS / 2016. From the results of this study indicate that, the application of the law where the judge as the applicator is in accordance with the values ​​of the law, and the community, but still very minimal or the need for more policies on victims of trafficking, namely the right to restitution (restoration of the rights of victims from trafficking).